2013
DOI: 10.1371/journal.pone.0070359
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Concentrations in Body Fluids after Implantation of Hip Replacements with Metal-on-Metal Bearing – Systematic Review of Clinical and Epidemiological Studies

Abstract: IntroductionThe use of metal-on-metal (MoM) total hip arthroplasty (THA) increased in the last decades. A release of metal products (i.e. particles, ions, metallo-organic compounds) in these implants may cause local and/or systemic adverse reactions. Metal ion concentrations in body fluids are surrogate measures of metal exposure.ObjectiveTo systematically summarize and critically appraise published studies concerning metal ion concentrations after MoM THA.MethodsSystematic review of clinical trials (RCTs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 75 publications
(127 reference statements)
5
53
0
2
Order By: Relevance
“…However, the reliability of metal ion levels for clinical prognostic remains questionable [17] with no clear cutoff values [19] and interlaboratory variability in measurements [21]. In addition, not all patients with high metal ion levels and high wear develop an adverse tissue reaction [4,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reliability of metal ion levels for clinical prognostic remains questionable [17] with no clear cutoff values [19] and interlaboratory variability in measurements [21]. In addition, not all patients with high metal ion levels and high wear develop an adverse tissue reaction [4,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison was made against a contemporary cohort of patients undergoing THA revision in the same period of time. We demonstrated that more than half of the HR patients suffered second or third grade acetabular defects according to the Paprosky classification [18]. In about three-fourths of the revisions an impaction bone grafting with either autogenous or allogenous cancellous bone was necessary.…”
Section: Discussionmentioning
confidence: 82%
“…pseudotumors) and ultimately lead to bone destruction. As increased ion blood levels may represent an indicator for HR failure, monitoring of ion blood levels is recommended in all patients [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ce dosage permet aussi de surveiller la performance de l'implant [29][30][31]. Par exemple, une prothèse mal positionnée ou présentant un défaut de conception s'usera anormalement entraînant une libération accrue d'élé-ments métalliques mis en évidence par le dosage du cobalt dans le sang circulant.…”
Section: Dosage Du Cobalt Et Recommandationsunclassified